Analysis of the Influence of Center tube on Cyclone Preheater Efficiency in Production Units in the Cement Industry - Susmanto, Prahady; Viola Yuliantika; Sryatin Arya (Journal of Chemical Process Engineering, 2025)
Cyclone Suspension preheater is an important part of the kiln unit which aims to separate materials and hot gases. The Suspension preheater consists of two strings, namely strings A and B and consists of 4 stages with stage 4 and stage 3 of string B not having a center tube. The efficiency calculation is carried out to determine the ability of the cyclone to separate material and gas and compare the efficiency of the cyclone which has a center tube with a cyclone without a center tube. The efficiency calculation is calculated using the Bohnet calculation. The efficiency calculation was obtained at stage 1 string A of 92.15%, stage 1 string B of 92.16%, stage 2 string A of 87.71%, stage 2 string B of 87.627%, stage 3 string A of 81.987%, stage 3 string B of 78.008%, stage 4 string A of 72.877%, and stage 4 string B of 73.459%. There was a decrease of 4% from stage 3 string A to stage 3 string B. A reduction in efficiency was observed in cyclones without a center tube. The gas flow in the cyclone is more regular with the presence of a center tube and has a longer residency time compared to a cyclone without a center tube. Acyclone without a center tube has a chaotic flow and turbulence can increase so that the separation between particles and gas is inefficient. The presence of a center tube effectively improves both separation efficiency and gas flow stability in the cyclone.